Pentagonal Shaped Fractal Band Notch Antenna using Parasitic Notch Filter - Shinde , P.; Shinde, J. (Journal of Scientific Research, 2025)
This paper presents the design of a band-notched simple iterative compact pentagonal fractal antenna. The antenna dimensions are W × L = 32 mm × 22 mm. The fractal radiating patch is placed on the front side of the FR 4 substrate material. The proposed fractal antenna geometry consists of a pentagon shape with three simple iterations of scale factor 0.62. The band-notched filter has been achieved by itching the pentagon shape as a parasitic patch on the back side of the substrate. The impedance bandwidth and reflection coefficient of the antenna are improved with the design of three iterations. The experimental results of the proposed CPW feed fractal antenna demonstrate wide band performance of 8.73 GHz ranging from 2.78 GHz to 11.51 GHz except the notched band frequency and exhibit peak gain of 8 dBi. The electromagnetically coupled pentagon parasitic patch is effectively optimized with respect to side length and position for notch-band development at 5.6 GHz, 9.3 GHz, and 12.5 GHz. These notch bands reject the interference of the 802.11a WLAN band and the lower spectrum of the X-band. The experimental radiation patterns are omnidirectional in the H-plane and bidirectional pattern in the E-plane. The proposed antenna is fabricated, and experimental results are verified on a vector network analyzer.